PEMBERDAYAAN PENGRAJIN KORAN BEKAS SATYA BALI KREATIF DI DESA SUMERTA KAUH KOTA DENPASAR - Ida Ayu Surasmi; AA Media Martadiani; A.A Bagus Amlayasa; Nyoman Senimantara (JURNAL SEWAKA BHAKTI, 2020)
Craft products from used newspaper waste are classified as rare, because the process is very complicated and the results are high quality so that many consumers are interested, especially for religious ceremonies in Bali. In addition to producing handicraft products from used newspaper and plastic materials, Mitra Satya Bali Kreatif, also participates in providing education or education and training to the community. The problems faced by partners include the limited knowledge in calculating the Cost of Production in an accurate and precise manner and do not have a digital marketing system. The result of this community partnership program is that partners understand how to calculate the cost of goods manufactured accurately and accurately and precisely so that the selling price of handicraft products can compete competitively in the market, there is a desire from partners to increase the marketing of handicrafts that already use information technology and media communication social, as well as partner motions in realizing a more optimal KUEP, so that in the future it can be more effective and independent and sustainable